Spectrometry analysis on Cyanobacteria for heavy metals detection in aquatic environment - Wong, Ling Shing; Voon, Betty Wan Niu; Teo, Siok Chin; Balakrishnan, Arutchelvam (EM International, 2016)
In this paper, we reported a method to detect the presence of Pb and Cu in aquatic environment using two types of photosynthetic pigments in cyanobacteria Anabaena cylindrica (Wong) chlorophylls and carotenoids as reporters. The detection was based on the reduction of chlorophylls and carotenoids in the presence of the heavy metals, while the changes were captured using spectrophotometer with ë = 440 nm and 640 nm respectively. Using cells from lag phase and the exposure time of 24 hours, the changes of both pigments were recorded after the cells were exposed to 0.01 mg/L, 0.10 mg/L, 1.00 mg/L, and 10.00 mg/L of Pb and Cu respectively. The results showed the optical densities (OD) which are corresponding to the concentration of chlorophylls and carotenoids in cyanobacteria were well-correlated to the change of heavy metals concentrations. Then, we demonstrated that the correlation between the concentration changes of the pigments to heavy metals and the sensitivity of the detection could be enhanced with simple modelling. Thus, we concluded that both chlorophyll and carotenoids in A. cylindrica could be used as bio-reporters for Pb and Cu detection, while modelling of the responses could be an alternative to enhance the sensitivity of the detection.